Entre desafios e conquistas: uma reflexão sobre a trajetória acadêmica no curso de medicina da UFSCar - Santos, Gabriel Giroldo dos (Universidade Federal de São Carlos, 2025)
This paper presents a reflective analysis of the academic journey throughout the Medical School at the Federal University of São Carlos (UFSCar). The text is organized into three axes corresponding to the course cycles: Basic Cycle, Clinical Cycle, and Internship. It discusses the main challenges faced, practical experiences, the impact of the COVID-19 pandemic on my education, and the lessons that contributed to both personal and professional growth over six years of training. The work emphasizes not only the development of technical skills but also the humanistic training and emotional maturity that characterize medical practice.
Between challenges and achievements: a reflection on the academic journey in the medical school at UFSCar
Keywords: Medicina; Formação médica; Graduação em saúde; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 3. Saúde e Bem-Estar